Akal dan Agama Perempuan (Perspektif Hadis Nabi dan Psikologi) - Ansori, Ibnu Hajar (Universum, 2018)
This article is a reinterpretation of the meaning of Hadith with the interconnection-integration paradigm, focused on the study of the Hadith about women's reason and religion through psychological approach. In the Hadith, Rasulullah stated that most of the inhabitants of hell are women, their minds are less (na>qis}a>t 'aql), their religion is also less (na>qis}a>t di>n). Textually, the word looks nuanced in gender discrimination. It seems to mean that women's intelligence is not as good as men's intelligence, neither religion nor faith-women are not as good as male religion. Therefore, it is understandable if the feminists call the element of misogyny in it. However, if examined contextually, based on the search asba>b al-wuru>d, the psychological study of women's reasoning and the study of the reality of their lives, it will come to the conclusion that there is no misogynous element in it. On the contrary, there are scientific cues that need further study behind the word. Some things that need further study as well as the formulation of the problem of this article is about to the reality of social life of women who attracted the attention of the Prophet, so he had a will to them to say istighfar more, a woman's brain changes with some sense function that distinguishes it from the male brain; including differences in hormonal changes and its adjustment to the menstrual cycle affecting some sense functions and diminish their role in spiritual activity.